Gelatin–Graphene Nanocomposites with Ultralow Electrical Percolation Threshold. Issue 32 (1st June 2016) - Nassira, Hoda; Sánchez‐Ferrer, Antoni; Adamcik, Jozef; Handschin, Stephan; Mahdavi, Hossein; Taheri Qazvini, Nader; Mezzenga, Raffaele
Abstract : Gelatin–graphene conductive biopolymer nanocomposites (CPCs) with ultralow percolation threshold are designed by reducing in situ graphene oxide nanosheets with ascorbic acid and suppressing the aggregation of the graphene nanosheets. The resulting conductive nanocomposites show a record‐low electrical percolation threshold of 3.3 × 10 −2 vol%, which arises from the homogeneous dispersion of the graphene nanosheets within the gelatin matrix.